Privacy and utility of genetic testing in families with hereditary cancer syndromes living in three countries: the international cascade genetic screening experience - Barnoy, Sivia; Dagan, Efrat; Kim, Sue; Caiata-Zufferey, Maria; Katapodi, Maria C.; , the CASCADE; , the K-CASCADE Consortia (Frontiers in Genetics, 2023)
Background: Hereditary breast and ovarian cancer and Lynch syndrome are associated with increased lifetime risk for common cancers. Offering cascade genetic testing to cancer-free relatives of individuals with HBOC or LS is a public health intervention for cancer prevention. Yet, little is known about the utility and value of information gained from cascade testing. This paper discusses ELSI encountered during the implementation of cascade testing in three countries with national healthcare systems: Switzerland, Korea, and Israel. Methods: A workshop presented at the 5th International ELSI Congress discussed implementation of cascade testing in the three countries based on exchange of data and experiences from the international CASCADE cohort. Results: Analyses focused on models of accessing genetic services (clinic-based versus population-based screening), and models of initiating cascade testing (patient-mediated dissemination versus provider-mediated dissemination of testing results to relatives). The legal framework of each country, organization of the healthcare system, and socio-cultural norms determined the utility and value of genetic information gained from cascade testing. Conclusion: The juxtaposition of individual versus public health interests generates significant ELSI controversies associated with cascade testing, which compromise access to genetic services and the utility and value of genetic information, despite national healthcare/ universal coverage.